English Medium Instruction in Multilingual Classroom of Community Schools of Nepal - Karki, Debraj (Journal of NELTA Gandaki, 2021)
Multilingualism and multilingual classroom are the reality of language education in Nepal. Teaching in multilingual classroom is both fascinating and challenging for teachers. The article aims at exploring how the monolingual ideology over English language teaching has created a gap between the linguistic capital of learners and the authoritative pedagogical practices of teachers. Taking case of a community school in Lalitpur district, I investigate the practices of teaching English to multilingual learners in a community school and explore pertinent issues of monolingual practices in a multilingual classroom. I draw data from informal telephonic talk to a subject teacher selecting purposively and observe the instructional practices in the linguistically diversified classroom. The article makes two major claims regarding the excessive use of monolingual teaching kills the inner potentialities of learners and suggests embodying multilingual pedagogy to foster learners’ epistemic growth in a natural and comfortable environment. The teachers should transform themselves to bring change and innovation in course of their pedagogical journey. Such kind of innovation is only feasible if teachers construct and reconstruct their pedagogical assumptions as of the need of learners. So that diversified learners are addressed properly in their knowledge gaining content. It further informs that immense investigation on language classrooms to bring a paradigm shift in English language education is essential in the days to go.